2009
DOI: 10.2166/wh.2009.032
|View full text |Cite
|
Sign up to set email alerts
|

Child dysentery in the Limpopo Valley: a cohort study of water, sanitation and hygiene risk factors

Abstract: The objective of this cohort study was to assess risk factors for child dysentery and watery diarrhoea. The study participants consisted of 254 children aged 12-24 months in rural South Africa and Zimbabwe in households where drinking water was collected from communal sources.The main outcome measure was the most severe diarrhoea episode: dysentery, watery diarrhoea or none. For dysentery, drinking water from sources other than standpipes had a relative risk ratio of 3.8 (95% CI 1.5-9.8). Poor source water qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 73 publications
0
13
0
3
Order By: Relevance
“…Vargas et al found that sporadic Shigella infections are more common in the dry than in the rainy season in Tanzania (P = 0.02) [21], a feature that agrees with the association of poor-quality water as the most significant risk factor for dystentery in the Limpopo Valley of southern Africa [138]. Shigella have a low infection dose, in part conferred by acid resistance that also makes survival in low-pH foods possible, and these bacteria have been isolated from a variety of street-vended foods in Addis Ababa, Ethiopia [139] and Accra, Ghana [140].…”
Section: Enteroinvasive E Coli and Shigellamentioning
confidence: 65%
“…Vargas et al found that sporadic Shigella infections are more common in the dry than in the rainy season in Tanzania (P = 0.02) [21], a feature that agrees with the association of poor-quality water as the most significant risk factor for dystentery in the Limpopo Valley of southern Africa [138]. Shigella have a low infection dose, in part conferred by acid resistance that also makes survival in low-pH foods possible, and these bacteria have been isolated from a variety of street-vended foods in Addis Ababa, Ethiopia [139] and Accra, Ghana [140].…”
Section: Enteroinvasive E Coli and Shigellamentioning
confidence: 65%
“…[30], [31] Four studies included the presence of blood or mucus in stool as part of their definition of diarrhea, [15], [17], [18], [32] and two studies [15], [17] reported dysentery as an outcome separate from “general” diarrhea; we did not include dysentery as a separate outcome in our review. Cohort studies in low-resource settings relied primarily on household surveillance and self-reported symptoms (e.g., maternal recall) for outcome assessment, using a range of recall periods (daily, up to one month; Tables 3 and 4); the two Canadian studies relied on monthly calendars maintained in the household and reported by telephone.…”
Section: Resultsmentioning
confidence: 99%
“…Des résultats d'analyses ponctuelles conformes ne peuvent assurer à eux seuls la qualité de l'eau de boisson en tout temps. Il faut donc prendre les précautions nécessaires pour assurer la salubrité et le bon fonctionnement d'un système individuel d'approvisionnement en eau de boisson (Gundry et al, 2009).…”
Section: Discussionunclassified
“…Un manquement à ces mesures de prudence pourrait favoriser la prolifération des bactéries. Pour assurer une désinfection efficace, l'eau qui alimente les systèmes de traitement pour l'élimination des microorganismes doit être claire et limpide (Gundry et al, 2009).…”
Section: Discussionunclassified
See 1 more Smart Citation